2008
DOI: 10.2478/v10078-008-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Oxidative Processes and Cytokine Response to Training in Professional Basketball Players

Abstract: In the present study, we evaluated the plasma concentration of inflammatory mediators including cytokines and their relation with oxidative damage markers in training cycles p<0.001) and p<0.001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…7 In addition, the cysteine derivative, GSH, is synthesized in erythrocytes and glutathione disulfide is transported outside the cell to maintain a high GSH/oxidized glutathione (GSSG) ratio. 3,29,30 Disulfide exchange reac-tions occur between protein thiols and low molecular weight disulfides. 3 Recently, Tsakiris et al 26 reported that vitamin E supplementation protected glucose-6-phosphate dehydrogenase activity in intense training.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, the cysteine derivative, GSH, is synthesized in erythrocytes and glutathione disulfide is transported outside the cell to maintain a high GSH/oxidized glutathione (GSSG) ratio. 3,29,30 Disulfide exchange reac-tions occur between protein thiols and low molecular weight disulfides. 3 Recently, Tsakiris et al 26 reported that vitamin E supplementation protected glucose-6-phosphate dehydrogenase activity in intense training.…”
Section: Discussionmentioning
confidence: 99%
“…TBARS has been used to detect lipid peroxidation in many body fluids and is a well established indirect measure of total oxidative stress (28)(29)(30)(31)(32)(33). A standard curve was generated for each assay run with malondialdehyde (MDA) provided by Cayman Chemical using a concentration range from 0 to 50 mmol/L.…”
Section: Measurement Of Lipid Peroxidationmentioning
confidence: 99%
“…TBARS assay was performed using a slight adaptation of the reference (Zembron-Lacny et al 2009). Stock solution contained 67 mg of thiobarbituric acid (Sigma-Aldrich) in 1 mL of dimethyl sulfoxide and 9 mL of deionized water.…”
Section: Tbars Assaymentioning
confidence: 99%